Designing with Computational Intelligence - Nedjah, Nadia; Lopes, Heitor Silvério; Mourelle, Luiza de Macedo (Studies in Computational Intelligence, 2017)
This book discusses a number of real-world applications of computational intelligence approaches. Using various examples, it demonstrates that computational intelligence has become a consolidated methodology for automatically creating new competitive solutions to complex real-world problems. It also presents a concise and efficient synthesis of different systems using computationally intelligent techniques.